The use of C3d as a means of monitoring clinical activity in systemic lupus erythematosus and rheumatoid arthritis. Issue 6 (December 1983) - Morrow, W J; Williams, D J; Ferec, C; Casburn-Budd, R; Isenberg, D A; Paice, E; Snaith, M L; Youinou, P; Le Goff, P
Abstract : Plasma samples from 44 patients with systemic lupus erythematosus (SLE) and 43 with rheumatoid arthritis (RA) were assayed for C3d, a breakdown product of the third component of complement (C3), which was also measured in parallel. Levels of C3d varied in direct proportion with disease activity in RA, whereas C3 showed little change. Although C3d values also increased with worsening clinical condition in SLE, this trend was not considered to be sufficiently clear to be useful and did not provide any advantage over the routinely performed C3 assay.